The politics of renewable power in Spain - John S. Duffield (European Journal of Government and Economics (EJGE), 2020)
Government support for renewable power in Spain has varied over time. After fostering a boom in the first decade of the 2000s, public support dried up in the early 2010s before making a reappearance in the last several years. This paper details and explains the fluctuating political fortunes of renewable power in Spain. It argues that the recent revival of support for renewable power should no come as no surprise. Rather, it reflects a reassertion of the underlying imperatives that prompted support by governments of different parties in previous years. Nevertheless, the role of government in promoting renewable power is now undergoing a fundamental change, as it shifts from directly subsidizing new generating capacity to removing barriers that might discourage private investment and facilitating the operation of market forces.
Keywords: Q42; Q48; 330; Spain; Spanish politics; renewable power; wind power; solar power